Using a learning environment perspective in evaluating an innovative science course for prospective elementary teachers - Martin-Dunlop, Catherine; Fraser, Barry (Springer, 2012)
This study is distinctive in that it employed a learning environment perspective in evaluating an innovative university science course for prospective elementary-school teachers. A sample of 525 fourth-year female students in 27 classes at a university in California responded to six learning environment scales selected mainly from the What Is Happening In this Class? (WIHIC) questionnaire, together with an enjoyment scale. Relative to a previous course, students in the innovative course perceived a more favourable classroom environment (in terms of cohesiveness, instructor support, investigation, cooperation, open-endedness and material environment) and enjoyed their classes more. All effect sizes were unusually large. Interviews with 35 students led to four themes: the lack of open-endedness in prior science courses compared with the innovative course; student groups not always automatically leading to class cohesion or cooperation; the appropriate balance in open-ended learning environments; and changes in attitudes towards science.